2020
DOI: 10.3390/nu12102992
|View full text |Cite
|
Sign up to set email alerts
|

Effective Immune Functions of Micronutrients against SARS-CoV-2

Abstract: The third coronavirus outbreak in the last two decades has caused significant damage to the world’s economy and community health. The highly contagious COVID-19 infection has affected millions of people to date and has led to hundreds of thousands of deaths worldwide. Aside from the highly infectious nature of SARS-CoV-2, the lack of a treatment or vaccine has been the main reason for its spread. Thus, it has become necessary to find alternative methods for controlling SARS-CoV-2. For the present review, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 109 publications
(109 reference statements)
1
37
0
4
Order By: Relevance
“…In particular, in Kurdistan is a place where the majority of the fruits and vegetables are imported products and border closing with neighboring countries made it difficult to be available. This could have negative effect on consumption of immune supporting micronutrients intake and overall well‐being (Junaid et al., 2020). However, the majority of the participants moderately adhered to Mediterranean diet as a healthy and recommended diet for COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in Kurdistan is a place where the majority of the fruits and vegetables are imported products and border closing with neighboring countries made it difficult to be available. This could have negative effect on consumption of immune supporting micronutrients intake and overall well‐being (Junaid et al., 2020). However, the majority of the participants moderately adhered to Mediterranean diet as a healthy and recommended diet for COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…258 In support of that, several studies across the world advocated the importance of a balanced diet with relevant nutrients and trace elements as an extenuation approach to build robust immune physiology to fight back the COVID-19 pandemic. 254,268,[278][279][280] Conclusion COVID-19 is a formidable challenge to the entire current world as there is no specified antiviral treatment possibility to date, thereby, preventive and control measures, or potent medicine available to fight the disease back. The host immune system plays pivotal roles against COVID-19 disease progression, similar to many other viral infections.…”
Section: Role Of Micronutrients Vitamins and Other Trace Elements Imentioning
confidence: 99%
“…A proper functioning of the human immune system is absolutely key to prevent the infections caused by a number of respiratory viruses (Calder et al, 2020a; Jayawardena et al, 2020 ). Among the factors that can significantly influence the role of the immune system to fight against these viruses – including SARS-CoV-2 – there is a notable influence of nutritional and nutrigenetic factors, including nutraceuticals ( Caccialanza et al, 2020 ; Calder 2020b; Di Stadio et al, 2020 ; Galmés et al, 2020 ; Jayawardena et al, 2020 ; Junaid et al, 2020 ; Iddir et al, 2020 ; Im et al, 2020 ). In relation to this, the European Safety Authority (EFSA) reported that six vitamins (A, B 6 , B 12 , C, D and folate), as well as four trace elements (zinc, selenium, copper and iron), were essential for the proper functioning of the immune system.…”
Section: Metals/metalloids the Immune System And Covid-19mentioning
confidence: 99%